Inteligencia lógico - matemática - Herrera Hidalgo, Paulina Jimena (2017)
Basic education is addressed towards the formation of reflective, proactive, qualified and human beings for life in society, mathematics learning is very important since, it is one of the educational areas for the existence of the student. It provides basic wisdom such as counting, grouping and selecting, allowing to be the necessary basis for its valuation. This research project intends to establish the incidence of the development of logical - mathematical intelligence in the teaching and learning process of the students of the 4th Year of General Basic Education in "Vicente León" Educational Unit, during 2016-2017. It was possible to demonstrate the lack of mastery of methodological strategies by the teachers, who carried out the entire teaching-learning process, without motivation, without play full strategies, which caused students to have difficulty in developing Logical-mathematical intelligence, in this way the students fulfilled the activities by obligation, without desire, by exigency, which produces an insignificant judgment. In mathematical logic, we refer to the logic that is in charge of studying valid or true statements, the relation of consequence between said statements, in order that their principles are oriented to a logical, critical and creative reasoning....